Splenic Rupture Secondary to Vascular Ehlers–Danlos Syndrome Managed by Coil Embolization of the Splenic Artery - Kamalanathan, Keisha C.; Barnacle, Alex M.; Holbrook, Charlotte; Rees, Clare (European Journal of Pediatric Surgery Reports, 2019)
Aim Atraumatic splenic rupture is uncommon and life-threatening. It may be related to underlying pathology and be the initial manifestation of the condition. Vascular Ehlers–Danlos syndrome (V-EDS) is a rare autosomal dominant collagen vascular disorder, associated with vessel fragility and rupture. We describe a child presenting with splenic rupture managed by embolization of the splenic artery. She was subsequently diagnosed with V-EDS.Case Description A 11-year-old girl with thalassemia trait presented with sudden onset of abdominal pain and hypovolemic shock. There was no history of trauma. Following resuscitation, abdominal computed tomography showed hemoperitoneum and active splenic arterial extravasation. Angiography demonstrated four bleeding points, from irregular vessels supplying the upper two-thirds of the spleen. These were not amenable to supraselective embolization. Therefore, coil embolization of the main splenic artery was performed, with no splenic supply seen on the postembolization angiogram. Her postoperative recovery was complicated by pancreatitis secondary to partial ischemia of the pancreatic tail. Subsequent extensive investigations excluded hematological, myeloproliferative, and infective causes for her splenic rupture. A safeguarding investigation was completed, with no pertinent factors identified. Findings of thin skin, abnormal bruising, and hypermobile joints raised a clinical suspicion of a connective tissue disorder. Genetic testing revealed a de novo mutation of the COL3A1 gene.Conclusions There are only four reports of V-EDS causing splenic rupture in the literature to date. These patients were all adults and only one had not previously been diagnosed with V-EDS. All underwent splenectomy. While V-EDS presenting with abdominal visceral rupture in children has been reported, this is the first report of a child with V-EDS presenting with splenic rupture. It is the only case of splenic rupture secondary to V-EDS that has been managed minimally invasively by embolization.
Keywords: splenic rupture; embolization; Ehlers–Danlos syndrome; vascular EDS; pediatric